Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s12884-020-02895-y
|View full text |Cite
|
Sign up to set email alerts
|

A case of successful maintained pregnancy after neoadjuvant chemotherapy plus radical surgery for stage IB3 cervical cancer diagnosed at 13 weeks

Abstract: Background: Cervical cancer during pregnancy is rare. The management for stage IB3 during pregnancy remains unclear and challenging. We report a successful preserved pregnancy in a stage IB3 patient who was treated with neoadjuvant chemotherapy (NACT) plus radical surgery. Case presentation: A 36-year-old pregnant woman was diagnosed with a 5-cm-diameter stage IB3 squamous cell carcinoma of the uterine cervix at 13 gestational weeks. The patient received 5 courses of systemic chemotherapy with carboplatin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The efficacy of NACT has long remained a mystery, with only a few trials investigating this matter. 14 Previous studies found that the rate of optimum response (reduction of tumor volume by >50%) following NACT was 78.8% in stage IB bulky tumors, however it reduced to only 60.7% in tumors with largest diameter of >2 cm. 20 , 21 Our case questions the effectiveness of NACT as her lesion increased in size after NACT completion.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The efficacy of NACT has long remained a mystery, with only a few trials investigating this matter. 14 Previous studies found that the rate of optimum response (reduction of tumor volume by >50%) following NACT was 78.8% in stage IB bulky tumors, however it reduced to only 60.7% in tumors with largest diameter of >2 cm. 20 , 21 Our case questions the effectiveness of NACT as her lesion increased in size after NACT completion.…”
Section: Discussionmentioning
confidence: 95%
“…13 The carboplatin and paclitaxel regimen is preferred compared to cisplatin and paclitaxel because it is better tolerated with reduced risk of ototoxicity and nephrotoxicity. 5,14 In this present case, after thorough discussion with a multidisciplinary team, we opted for neoadjuvant chemotherapy with paclitaxel 175mg/m 2 and carboplatin 6 AUC as a 3-weekly regimen started at 14 weeks gestational age.…”
Section: Dovepressmentioning
confidence: 94%
“…Based on the results of several prospective trials, Platinum-based chemotherapy with either Paclitaxel or Docetaxel represents the most prescribed regimen in the neo-adjuvant setting [127]. This regimen has been widely used across trials [62,69,[82][83][84][85]87,88,90,92,103,104,106,108,109,111,112,121,[128][129][130][131][132][133][134][135][136][137][138][139][140] and was usually associated with a favorable tolerance profile, with no report of grade 3-4 adverse events. General guidelines advocate in favor of the use of Carboplatin instead of Cisplatin in pregnant women to avoid ototoxicity in children exposed in utero.…”
Section: Chemotherapymentioning
confidence: 99%
“…Cervical cancers in pregnancy are mostly diagnosed at early stages and have favorable outcomes ( 1 ); however, stage IB3 tumors remain a challenge for physicians ( 2 ). In addition, pregnant patients with cervical lesions show a relatively high proportion of combined high-risk human papillomavirus infections ( 3 ).…”
mentioning
confidence: 99%